PERBANDINGAN SENSITIVITAS NANOPARTIKEL PERAK DENGAN REDUKTOR ALBUMIN DARI TELUR AYAM DAN BEBEK UNTUK ANALISIS MERKURI - Fikri Fadillah Azhar; Elvinawati Elvinawati; Nurhamidah Nurhamidah (University of Bengkulu, 2019)
The aims of this study were determine the protein level of chicken egg albumin (Gallus Sp.) And duck egg albumin (Anas domestica) also optimum conditions, sensitivity, and LOD values of silver nanoparticles (NPP) synthesized using bioreductors of chicken (Gallus Sp.) egg albumin and duck (Anas domestica) egg albumin for analysis of mercury ions (II). This research was conducted at the Laboratory of Chemistry FKIP UNIB on April - July 2019. Protein levels of chicken egg albumin and duck egg albumin were obtained in the amount of 0.210 gr / 100 ml and 0.234 gr / 100ml, respectively. The NPP synthesized in this study was carried out by mixing silver precursors derived from 10 mM AgNO3 solution and 1% albumin solution as bioreductors of each chicken egg albumin solution and duck egg albumin. The optimum condition of NPP synthesized using chicken egg albumin bioreductor and duck egg albumin was the same, with the number of comparisons between AgNO3 and albumin solutions namely 1: 2 and stirring time of 30 minutes. The results showed that NPP synthesized using chicken egg albumin and egg albumin ducks had good sensitivity to Hg metal with the addition of Hg metal concentrations above 50 ppm that be marked with significant color changes from brownish yellow to clear. LOD values in each NPP synthesized using bioreductors of chicken egg albumin and duck egg albumin were 3334 ppm and 2,238 ppm, so that NPP synthesized using bioreductor of duck egg albumin was more sensitive than NPP synthesized using bioreductor of chicken egg albumin for mercury metal analysis. This is influenced by the differences of protein levels of chicken egg albumin and duck egg albumin where the protein level of duck egg was higher than the protein level of chicken egg.